Pilot‐scale cellulosic ethanol production using eucalyptus biomass pre‐treated by dilute acid and steam explosion. (29th April 2016) - McIntosh, Shane; Zhang, Zhanying; Palmer, Janice; Wong, Heng‐Ho; Doherty, William O.S.; Vancov, Tony
Abstract: The widespread deployment of commercial‐scale cellulosic ethanol currently hinges on developing and evaluating scalable processes whilst broadening feedstock options. This study investigates whole Eucalyptus grandis trees as a potential feedstock and demonstrates dilute acid pre‐treatment (with steam explosion) followed by pre‐saccharification simultaneous saccharification fermentation process (PSSF) as a suitable, scalable strategy for the production of bioethanol. Biomass was pre‐treated in dilute H2 SO4 at laboratory scale (0.1 kg) and pilot scale (10 kg) to evaluate the effect of combined severity factor (CSF) on pre‐treatment effectiveness. Subsequently, pilot‐scale pre‐treated residues (15 wt.%) were converted to ethanol in a PSSF process at 2 L and 300 L scales. Good polynomial correlations (n = 2) of CSF with hemicellulose removal and glucan digestibility with a minimum R 2 of 0.91 were recorded. The laboratory‐scale 72 h glucan digestibility and glucose yield was 68.0% and 51.3%, respectively, from biomass pre‐treated at 190 °C /15 min/ 4.8 wt.% H2 SO4 . Pilot‐scale pre‐treatment (180 °C/ 15 min/2.4 wt.% H2 SO4 followed by steam explosion) delivered higher glucan digestibility (71.8%) and glucose yield (63.6%). However, the ethanol yields using PSSF were calculated at 82.5 and 113 kg/ton of dry biomass for the pilot and the laboratory scales, respectively. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd